Program Kajian Kitab Ushfuriyah Untuk Menumbuhkan Karakter Islami Di Masjid Nurul Hasani - Jami' Shobri; Nelud Daraajatul Aliyah (Jurnal Riset Pendidikan Multidisiplin dan Pengabdian Kepada Masyarakat, 2025)
This Community Service Program (PKM) aims to foster Islamic character among teenagers through the study of the Ushfuriyah book at the Nurul Hasani Mosque, Kraton District. This activity uses an Asset-Based Community Development (ABCD) approach that focuses on exploring and utilizing local community assets as a basis for community empowerment. The implementation stages include mapping community assets, mobilizing assets through program design, participatory implementation of activities, and reflective evaluation of learning outcomes. The program results show a significant improvement in three main areas of character building among participants, namely cognitive, affective, and psychomotor. In the cognitive aspect, participants showed an increase in understanding of moral values such as honesty, trustworthiness, and sincerity integrated with social reality. In the affective aspect, spiritual awareness, empathy, and internal motivation to improve oneself grew. Meanwhile, in the psychomotor aspect, there was visible behavior in the form of discipline, social involvement, and responsibility in mosque activities. These results prove that the study of classical texts can play a strategic role in Islamic character building for youth when packaged in a participatory, contextual, and community-based manner. Thus, the mosque once again functions as a center for moral formation and social transformation in the community.